Development of a Predictive Pharmacophore Model and a 3D-QSAR Study for an in silico Screening of New Potent Bcr-Abl Kinase Inhibitors - Vrontaki, Eleni; Melagraki, Georgia; Voskou, Stella; S. Phylactides, Marios; Mavromoustakos, Thomas; Kleanthous, Marina; Afantitis, Antreas (Mini Reviews in Medicinal Chemistry, 2017)
Chronic myelogenous leukemia (CML) is a myeloproliferative disorder, characterized, in most cases, by the presence of the Bcr-Abl fusion oncogene. Bcr-Abl is a constitutively active tyrosine kinase that is responsible for the malignant transformation. Targeting the Bcr-Abl kinase is an attractive treatment strategy for CML. First and second generation Bcr-Abl inhibitors have focused on targeting the ATP-binding domain of the kinase. Mutations in that region are relatively resistant to drug manipulation. Therefore, non-ATP-competitive agents have been recently developed and tested. In the present study, in an attempt to aid the design of new chemotypes with enhanced cytotoxicity against K562 cells, 3D pharmacophore models were generated and 3D-QSAR CoMFA and CoMSIA studies were carried out on the 33 novel Abl kinase inhibitors (E)-α-benzylthio chalcones synthesized by Reddy et al. A five-point pharmacophore with a hydrogen bond acceptor, two hydrophobic groups and two aromatic rings as pharmacophore features, and a statistically significant 3D-QSAR model with excellent predictive power were developed. The pharmacophore model was also used for alignment of the 33 compounds in a CoMFA/CoMSIA analysis. The contour maps of the fields of CoMFA and CoMSIA models were utilized to provide structural insight into how these molecules promote their toxicity. The possibility of using this model for the design of drugs for the treatment of β-thalassemia and sickle cell disease (SCD), since several Bcr-Abl inhibitors are able to promote erythroid differentiation and γ-globin expression in CML cell lines and primary erythroid cells is discussed.
Keywords: Chalcones